Absolute quantification of gene expression in drug discovery using RT-qPCR: Case of a drug used in the treatment of leishmaniasis - Charbel Al Khoury (13167975) (2022)
Leishmaniasis is a neglected disease and a public health concern. Chemotherapeutic agents available for the treatment of parasitic infections, including leishmaniasis, have several limitations. For that, we designed a highly sensitive assay using RT-aqPCR to evaluate the efficacy of antileishmanial drugs using SYBR Green to quantify the expression of marker genes. A matrix of reactions using different annealing temperatures and primer concentrations was tested to obtain optimum assay performance. The standard curves designed for quantification of parasites and macrophages showed linearity over a 9-log DNA concentration range. The amount of input target sequence was determined by plotting the Ct value of drug-exposed cells on the standard curves. We then tested the efficacy of miltefosine against Leishmania tropica. The RT-aqPCR assay was more sensitive, reproducible, and time-efficient than the conventional microscopic counting method. Most of the anti-parasitic drugs available have significant drawbacks, and there is an urgent need to develop new alternatives. Our assay expedites preclinical testing efficacy of candidate anti-parasitic compounds. Other Information Published in: Research in Veterinary Science License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.rvsc.2022.10.012